PERFORMANCE ANALYSIS ON FREIGHT TRANSPORTATION IN FURNITURE INDUSTRY, A CASE STUDY IN BANTUL, YOGYAKARTA, INDONESIA - C. H. Soekamto; S. Priyanto (Journal of the Civil Engineering Forum, 2012)
The Supply Chain Management is a new philosophy encouraging internal and external integration which encompass all the aspects, from the supplier until down to the customers. Transportation plays a major role in achieving efficiency and effectiveness because the role of transportation in the Supply Chain is as the intermediary help to distribute the physical goods from one entity to another entity.  For this reason, the objective of this research is to analyse and measure the effectiveness and efficiency of inbound and outbound logistics in the furniture industry in Bantul, Yogyakarta. Firstly, the author will try to draw the supply chain mapping in order to gain more understanding about the entities in the supply chain.  Secondly, performance of the transportation modes that will be used to move the furniture will be assessed through questionnaire. Thirdly, the author will try to analyse the response if rail transportation is proposed as an alternative transportation mode to move the goods. Lastly, conclusion and recommendation regarding the issue will be derived as implied in the result from data analysis. Keywords: Supply chain management, transportation, performance, furniture industry.